A Comparison on Effects of High Dose Rosuvastatin versus High Dose Atorvastatin on Lipid Profile and CRP Level in Patients Undergoing Percutaneous Coronary Intervention: A Randomized Study - Mahboubeh Darban; Elham Yusefabadi; Majid MirmohammadKhani; Bahram Sohrabi; Bahador Bagheri (Tabriz University of Medical Sciences, 2021)
Background: Statins are the most common drugs used for reducing low-density lipids (LDL). In addition to their lipid-lowering effects, they have well-documented anti-inflammatory actions. The goal of this study was to compare the effects of high dose atorvastatin and rosuvastatin on lipid profiles and high sensitivity C Reactive Protein (hs-CRP) in patients undergoing percutaneous coronary intervention (PCI). Methods: The study was done between October 2017 and September 2018 in Semnan KowsarHospital. In this randomized trial, 69 patients with atherosclerotic coronary artery disease were randomly assigned 1:1 to receive atorvastatin (80 mg daily) or rosuvastatin (40 mg daily) for4 months. Levels of hs-CRP and lipid profiles including cholesterol, triglyceride, low-density lipids (LDL), and high-density lipids (HDL) were measured and compared before and after the treatments. Lipid profiles were measured at baseline, 2 months, and 4 months of the treatment. Results: Sixty patients completed the study. The mean age was 61.1 ± 6.6 years with an excess of males. After 4 months, both drugs could significantly reduce LDL levels, however, the between-group differences were not statistically significant. Rosuvastatin significantly increased HDL levels (p < 0.05). In addition, triglyceride levels had a significant reduction in both groups, yet the differences were not significant. Both drugs caused significant reductions in hs-CRP levels(p < 0.05). Moreover, the effects of treatments were seen in drug naïve patients as well as patients who were on statins prior to the trial. Conclusion: The results indicate that high dose therapies with atorvastatin and rosuvastatin have similar effects on lipid profiles and hs-CRP levels in patients undergoing PCI.